Risk of Early Mortality in Patients With Newly Diagnosed Multiple Myeloma. Issue 50 (December 2015) - Hsu, Pei; Lin, Ting-Wei; Gau, Jyh-Pyng; Yu, Yuan-Bin; Hsiao, Liang-Tsai; Tzeng, Cheng-Hwai; Chen, Po-Min; Chiou, Tzeon-Jye; Liu, Jin-Hwang; Liu, Yao-Chung; Liu, Chia-Jen
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: The overall survival of patients with multiple myeloma (MM) has been improved greatly over the last 2 decades with the broader use of novel drugs and autologous tandem transplantation. However, more than one tenth of myeloma patients still die shortly after diagnosis. We therefore aim to investigate the risk factors of early mortality (death within 60 days after diagnosis) in patients with MM. We included in this study 451 consecutive patients with MM, newly diagnosed at an Asian tertiary medical center between January 1, 2002 and April 30, 2015. A total of 57 subjects who experienced early mortality were identified. Risk factors for early mortality in myeloma patients were collected and analyzed. Early mortality occurred in 57 (12.6%) of the myeloma patients. In the multivariate analysis, being male (adjusted OR 2.93, 95% CI 1.17–7.31), primary plasma cell leukemia (adjusted OR 17.61, 95% CI 1.01–306.05), serum albumin < 3.5 g/dL (adjusted OR 2.70, 95% CI 1.15–6.38), corrected serum calcium ≥ 12 mg/dL (adjusted OR 2.94, 95% CI 1.21–7.14), and LDH ≥ 250 U/L (adjusted OR 3.07, 95% CI 1.50–6.27) were identified as independent risk factors of early mortality. Pneumonia with other infections contributed most to early mortality (n = 36, 65%), followed by renal failure and cardiac failure. The early mortality rate is high (12.6%) in patients with MM. Patients who are male and those with primary plasma cell leukemia, low serum albumin, high-corrected serum calcium, or LDH are at risk of early mortality. Nearly two thirds of the myeloma patients who experienced early mortality in our study (37 of 57, 65%) died of infection. Once a high-risk group is identified, much effort is required to target new approaches for prevention, early detection, and treatment of infections.